The Differences of Plaque pH between Consumption of Sucrose Chocolate and Stevia Chocolate in Children aged 10-12 Years - Saputra, Muhammad Rhaufly Dwi Arga; Kaswindiarti, Septriyani; Murdiyanto, Dendy; Anwaristi, Aprilia Yuanita (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Introduction: Chocolate is a popular sweet treat among children. The sugar used in chocolate can lead to the development of dental plaque and impact the process of teeth demineralization and remineralization. Until now, there has not been much research on how the acidity of dental plaque differs when children aged 10-12 consume chocolate sweetened with sucrose compared to chocolate sweetened with stevia. This study aims to explore and compare the effects of sucrose chocolate and stevia chocolate on the acidity of dental plaque in children aged 10-12 years. Methods: In this study, the researchers employed quasi-experimental research methods. The research received approval from the Ethical Committee of Health Research at Dr. Moewardi General Hospital, indicated by Ethical Clearance Number 1.884/X/HREC/2023. Initially, on the first day, the researchers measured the plaque pH of twenty-one children aged 10-12 years from SD Muhammadiyah 1 Surakarta. This measurement was done before any intervention by using an excavator on all surfaces of their back teeth – the outer, inner, and in-between surfaces. The researchers combined the collected plaque with 2.5 ml of deionized water in a properly labelled sterile container. The plaque pH was measured using a pH metre (Hanna, Romania), calibrated beforehand with a pH 7 solution. The subjects then consumed 30% sucrose chocolate for 60 seconds. Twenty minutes after this intervention, the researchers measured the plaque pH using the same method. On the second day, the same subjects were instructed to consume 1% stevia chocolate, again using the same method. The results, specifically the average difference in plaque pH before and after the interventions on the two days, were analysed using an independent T-test. Results: The findings revealed that the average plaque pH before eating sucrose chocolate was 6.6222 ± 0.13137, and after consumption, it decreased to 6.2794 ± 0.11425. Before consuming stevia chocolate, the average plaque pH was 6.6746 ± 0.13536, and after consumption, it decreased to 6.4794 ± 0.13059. The average difference in plaque pH before and after consuming sucrose chocolate was 0.3429 ± 0.08508, whereas for stevia, it was 0.1952 ± 0.08517. According to the independent t-test, there was a notable difference in plaque pH between children aged 10-12 years who consumed sucrose chocolate and those who consumed stevia chocolate (p<0.05). Conclusion: Based on the findings from the study comparing the plaque pH in 10-12-year-old children after consuming sucrose chocolate and stevia chocolate, it can be concluded that there is indeed a disparity in plaque pH between the two types of chocolate. Specifically, the plaque pH in children who consumed sucrose chocolate was lower than that in those who consumed stevia chocolate.